2004
DOI: 10.1007/s11103-004-0237-8
|View full text |Cite
|
Sign up to set email alerts
|

PVX-Cre-mediated marker gene elimination from transgenic plants

Abstract: Cre recombinase gene from bacteriophage P1 was transiently expressed by a Potato Virus X (PVX)-based vector in transgenic lox-target Nicotiana benthamiana plants to remove the selectable marker gene. The target construct consisted of two directly oriented lox sites flanking a bar gene located between a gfp coding region and an upstream CaMV 35S promoter. The Cre-mediated excision of intervening sequence placed the gfp coding region under the transcriptional control of the CaMV 35S promoter. GFP activity was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 48 publications
2
38
0
Order By: Relevance
“…The selection marker removal may significantly reduce the public acceptance of genetically modified plants (Miki and McHugh, 2004). Several marker elimination methods in higher plants have been developed during these years including co-transformation, which is usually applied in Agrobacterium-mediated transformation (Sripriya et al, 2008) and various site-specific recombination methods that eliminate the selection marker by deleting or inverting the marker gene with the help of an enzyme recombinase (Cotsaftis et al, 2002;Darbani et al, 2007, Kopertekh et al, 2004, Ow, 2002. The marine algal genetic transformation will certainly meet these biosafety issues (more discussion can be found in Section 6) when cultivating transgenic microalgae in an open pond of a coastal area or transgenic macroalgal sporophytes in the open sea.…”
Section: Reporter and Marker Genesmentioning
confidence: 99%
“…The selection marker removal may significantly reduce the public acceptance of genetically modified plants (Miki and McHugh, 2004). Several marker elimination methods in higher plants have been developed during these years including co-transformation, which is usually applied in Agrobacterium-mediated transformation (Sripriya et al, 2008) and various site-specific recombination methods that eliminate the selection marker by deleting or inverting the marker gene with the help of an enzyme recombinase (Cotsaftis et al, 2002;Darbani et al, 2007, Kopertekh et al, 2004, Ow, 2002. The marine algal genetic transformation will certainly meet these biosafety issues (more discussion can be found in Section 6) when cultivating transgenic microalgae in an open pond of a coastal area or transgenic macroalgal sporophytes in the open sea.…”
Section: Reporter and Marker Genesmentioning
confidence: 99%
“…Two Cre-virus vectors, PVX-Cre (Kopertekh et al, 2004a(Kopertekh et al, , 2004b and TMV-Cre (Jia et al, 2006), have been shown to be functional in loxtarget N. benthamiana and N. tabacum plants. In both vectors the cre gene was integrated between movement and coat protein genes.…”
Section: Cre Expression Strategies: Efficiency and Limitationsmentioning
confidence: 99%
“…Another option to perform transient cre expression is the use of Cre-virus vectors. The first plant Cre-virus vector was based on PVX and demonstrated high recombination rates (48-82%) in N. benthamiana (Kopertekh et al, 2004b). This vector was also suitable to generate marker-free tobacco plants without a regeneration step (Kopertekh et al, 2004a).…”
Section: Cre-mediated Excision Of Marker Genesmentioning
confidence: 99%
“…The most frequently used recombination approach in transgenic plants is the Cre/lox system. Recombination events have also been achieved in animal and plant systems (Kopertekh et al 2004).…”
Section: Introductionmentioning
confidence: 99%